Time to SARS‐CoV‐2 clearance among patients with cancer and COVID‐19. (9th February 2021) - Xu, Wenxin; Piper‐Vallillo, Andrew J.; Bindal, Poorva; Wischhusen, Jonathan; Patel, Jaymin M.; Costa, Daniel B.; Peters, Mary Linton B.
Abstract: Background: For cancer patients, coronavirus disease 19 (COVID‐19) infection can lead to delays in cancer therapy both due to the infection itself and due to the need to minimize exposure to other patients and to staff. Clearance guidelines have been proposed, but expected time to clearance has not been established. Methods: We identified all patients at a tertiary care hospital cancer center between 25 March 2020 and 6 June 2020 with a positive nasopharyngeal reverse transcriptase polymerase chain reaction (RT‐PCR) test for the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), a cancer‐related visit within 3 years, and at least one follow‐up assay. We determined the time to clearance using American Society of Clinical Oncology (ASCO), the UK National Institute for Health and Care Excellence (UK‐NICE), and Centers for Disease Control and Prevention (CDC) criteria. A matched non‐cancer comparison cohort was also identified. Results: Thirty‐two cancer patients were identified. Nineteen were cleared by ASCO criteria, with estimated median time to clearance of 50 days. Fourteen patients resumed chemotherapy prior to clearance. Using UK‐NICE criteria, median time to clearance would have been 31 days, and using CDC criteria, it would have been 13 days. The matched non‐cancer cohort had similar clearance time, but with less frequent testing. Conclusion: SARS‐CoV‐2 clearance times differ substantially depending on the criteria used and may be prolonged in cancer patients. This could lead to a delay in cancer care, increased use of clearance testing, and extension of infection control precautions. Abstract : In this single‐institution retrospective cohort study, the median time to SARS‐CoV‐2 clearance among cancer patients was 50 days using the ASCO/CDC criteria of two negative RT‐PCR assays >24 h apart. Using alternative criteria of one negative RT‐PCR assay (UK‐NICE) or CDC clinical criteria (10 days after first positive RT‐PCR and 3 days after last symptoms), median clearance times were 31 and 13 days, respectively.